Alice Walker’s The Color Purple From Being Silent to Having A Voice: Struggling to Achieve Self-Empowerment - Al-Wazir, Abd Alrahmain Badr Ibrahim (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The colonial period is the starting point for America’s long history of racism and violence towards people of color, particularly African Americans. The relationship between Whites and Blacks in this racist American culture was predicated on two principles: White hegemony and Black subordination. This case is why Black people have long fought for freedom in every arena. Because of this, black authors have retooled their writings to advocate for black causes and preserve African-American culture. Novelist and feminist Alice Malsenior Walker are included in this group. Her writings explore the significance of women of color throughout history. She is out as bisexual and accepts individuals of various orientations, backgrounds, and identities. She has detailed the racial, social, and ethnic subjugation that African-American men and women have endured. The Color Purple has shed light on the struggles of those at the bottom of society. This paper delves into the significant feminist themes and examines how a black woman can rebel and establish a voice away from a patriarchal society. In her book, Walker outlines the discrimination and suffering experienced by black women and offers some potential answers. The Color Purple features strong female characters like Celie, Shug, Nettie, and Sofia, who face challenges but ultimately overcome them. At the novel’s end, Celie’s transformation is remarkable as she becomes an independent and liberated woman, free from the oppression and abuse she once endured. She has transformed from her previous appearance to a stunning swan. She has made incredible progress, transitioning from burdening to expressing her physical and mental independence and reuniting with her friends and sister.